2017
DOI: 10.1111/imj.13525
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism management in Northeast Melbourne: how does it compare to international guidelines and data?

Abstract: While our 'real-world' VTE experience during the warfarin era largely correlates with international guidelines, there remains heterogeneity in the management strategies, including excessive thrombophilia screening and longer duration of anticoagulation. This audit highlights the need for national VTE guidelines, as well as prospective auditing of VTE management, in the direct oral anticoagulant era for future comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Although these disorders are found in~5-10% of patients with a first VTE incident, they may not be independent risk factors for recurrent thrombosis. After adjustment for age, sex, and anticoagulant use, these thrombophilia disorders are only associated with a relatively low (~1.5-fold increase) risk of VTE recurrence compared to their non-thrombophilia patient counterparts [36][37][38][39]. Observations from recent case reports and case series on efficacy of DOACs in patients with FVL or PT G20210A mutation are mostly in line with our favorable subgroup analysis results, supporting the use of DOACs in these low-risk thrombophilias (Table S5) [40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Although these disorders are found in~5-10% of patients with a first VTE incident, they may not be independent risk factors for recurrent thrombosis. After adjustment for age, sex, and anticoagulant use, these thrombophilia disorders are only associated with a relatively low (~1.5-fold increase) risk of VTE recurrence compared to their non-thrombophilia patient counterparts [36][37][38][39]. Observations from recent case reports and case series on efficacy of DOACs in patients with FVL or PT G20210A mutation are mostly in line with our favorable subgroup analysis results, supporting the use of DOACs in these low-risk thrombophilias (Table S5) [40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, although most patients with PNH experience intravascular haemolysis and its associated risks, the requirement for transfusion is dependent not only on the degree of haemolysis but also on how well the bone marrow is capable of compensating for the loss. 13,22,23 Additionally, other factors, such as patient symptoms, physician practice patterns and local policies, impact the decision on whether to transfuse a particular patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent real-life VTE audit of more than 1,000 patients has shown that VTE recurrence rates remain substantial in patients with isolated distal DVT (IDDVT) and in those with minimally provoked VTE. 20 We demonstrated that VTE recurrence rates in the IDDVT population (16/166, 10%) were similar to those in major VTE (41/586, 7%; p ¼ 0.36), with 60% of patients with IDDVT suffering major recurring VTE. 21 Similarly, VTE recurrence risk remained substantial in patients with provoked VTE, especially in those due to nonsurgically related causes (3.4 per 100 person-years), and of note, patients with minimally provoked VTE, such as long travels, had similar recurrence rate compared with those with unprovoked VTE (5.8 vs. 4.6 per 100 person-years; RR: 1.30; 95% CI: 0.61-2.79; p ¼ 0.50).…”
Section: Clinical Risk Assessmentmentioning
confidence: 50%